1992
DOI: 10.2116/analsci.8.213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thorium, Uranium and Zirconium with Arsenazo III Using Third-Order Derivative Spectrophotometry

Abstract: Derivative spectrophotometry of the 3rd-order was used to determine microgram amounts of Th, U(VI) and Zr with Arsenazo III. Complexes of these metals with the reagent form in a strongly acidic (4 M HC10a) and 2-propanol-water (25%(v/ v)) medium. Optimal apparatus parameters and the way of obtaining derivative spectra were established. A determination of the Th and Zr sum is possible after measuring the derivative value at 673.4 nm (where the derivative spectrum of the U(VI)-Arsenazo III complex crosses the ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…It is widely used for analytical spectroscopy of zirconium (28,39) actinoids (40,41), and rare earth elements (42). Zr 4þ and its complexes with AHA lack an absorbance peak in the visible spectral range but zirconium will form complexes with AAIII (Eq.…”
Section: Complexation Of Zr With Arsenazo IIImentioning
confidence: 99%
“…It is widely used for analytical spectroscopy of zirconium (28,39) actinoids (40,41), and rare earth elements (42). Zr 4þ and its complexes with AHA lack an absorbance peak in the visible spectral range but zirconium will form complexes with AAIII (Eq.…”
Section: Complexation Of Zr With Arsenazo IIImentioning
confidence: 99%
“…5 Since derivative techniques have been widely applied: further development [6][7][8] and reviews were reported. [9][10][11][12][13][14][15][16][17] The main targets of reviews 17 were basic characteristics of DS and a few analytical applications of DS were given (The number of bibliographic references was 93).…”
mentioning
confidence: 99%
“…Differentiation of a zero order spectrum of a combination of components shows the way to derivative spectrum of any order. There are many methods are used for discrimination of a spectrum viz., by analog or numeric method, spectral differentiation may be deliberate either graphically on paper or registered in a computer memory [5]. Measurement of derivative spectra value is achieved out by three methods viz.…”
Section: Measurement Techniques Of the Derivative Spectroscopymentioning
confidence: 99%
“…Measurement of derivative spectra value is achieved out by three methods viz. graphic measurement, numeric measurement, zero crossing technique Graphic measurement Graphic measurement is theoretical method for calculate the derivative spectra on paper, its manual method it suffer from disadvantage that it gives inaccurate results because the value can determined numerically can be abolish or diminish beyond restriction [5].…”
Section: Measurement Techniques Of the Derivative Spectroscopymentioning
confidence: 99%